Interactive coercive relationship and spatio-temporal coupling coordination degree between tourism urbanization and eco-environment: A case study in Western China. (September 2022) - Ma, Mengyao; Tang, Jianxiong
Highlights: The eco-environment does not always deteriorate with the process of tourism urbanization. Expanded the research of EKC theory from the perspective of tourism urbanization and eco-environment. Introducing the gravitational model to explore the spatial connection of coupling coordination degrees. More attention should be paid to tourism urbanization in underdeveloped areas. Abstract: The deteriorating eco-environment is the key to restrict the development of tourism urbanization in the western region. Since the eco-environmental effects caused by tourism urbanization have complex interactions, how to coordinate the relationship between the two has become one of the most severe challenges for the sustainable development of western China and even the whole of China. Previous quantitative studies on the coupling coordination between tourism urbanization and eco-environment are limited because they ignore the interactive coercion relationship between complex systems and the spatial dynamic relationship of coupling coordination. Given this research gap, this research has constructed a new comprehensive evaluation index system of tourism urbanization and eco-environment. The interactive coercion model, the coupling coordination degree model and the gravity model are used to evaluate the interaction relationship, coupling coordination type and spatial connection strength between tourism urbanization and eco-environment in western China from 2005 to 2019. The main conclusions are as follows: (1) The level of tourism urbanization shows a rapid upward trend, and the eco-environment quality shows a fluctuating and low-speed upward trend; (2) The double exponential curve between tourism urbanization and eco-environment is an inverted U-shaped curve, and the empirical analysis confirms the Kuznets hypothesis; (3) The degree of coupling coordination has experienced a development process from "seriously unbalanced" to "superior balanced", and the interaction type has evolved into superior balanced-eco-environment lag; (4) The spatial connection of coupling coordination shows the characteristics of complication and gradient, and the interaction between provinces produces a pattern of adjacent associations. The results of this study are expected to implement an appropriate tourism urbanization development model in western China and provide decision support for the green and sustainable development of tourism urbanization and eco-environment in western China.